Social equity in governance of ecosystem services: synthesis from European treeline areas - Sarkki, Simo; Jokinen, Mikko; Nijnik, Maria; Zahvoyska, Lyudmyla; Abraham, Eleni; Alados, Concepcion; Bellamy, Chloe; Bratanova-Dontcheva, Svetla; Grunewald, Karsten; Kollar, Jozef; Krajci, Jan; Kyriazopoulos, Apostolos; et al. (Inter-Research, 2017)
Achieving social equity among local stakeholders should be a key objective for ecosystem service (ES) governance in Europe's ecologically fragile treeline areas. The ES literature tends to be biased towards distributional equity and market-based instruments when assessing social equity of ES governance. In this study, we analyze a wide range of social equity procedures that have been applied in Europe, using 11 synthesized case studies of governance-related challenges and 75 proposals for governance enhancement from 8 European countries provided by researchers with expertise on treeline area governance. The proposals were grouped by inductive clustering into 10 procedural or distributional equity-related policy recommendations: (1) increase stakeholder collaboration, (2) balance interactions between horizontal and vertical governance levels, (3) increase ES education, (4) use science to guide decisions, (5) start collaboration at an early stage, (6) enhance transparency, (7) aim to mitigate negative impacts, (8) use an ES approach to identify synergistic goals for governance, (9) enhance balanced multi-functional land use, and (10) use market-based instruments to balance benefits and costs deriving from governance decisions. Finally, we discuss 5 more general proposals on how regulatory and market-based approaches could be linked to enhance both procedural and distributional equity of treeline area governance.
Keywords: ekosysteemipalvelut; maankäyttö; ilmastonmuutokset; ecosystem services; land use; climate change; sosiaalinen oikeudenmukaisuus